2009
DOI: 10.1177/0042085909352583
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Worlds of Successful Cambodian American Students

Abstract: Educational policy usually overlooks Cambodian American students as a unique ethnic group, attending instead to the positive statistics that aggregate Asian American students into a single group of successful students. Through ethnographic interviews, this article examines how successful Cambodian American students interpreted values from their multiple worlds in relation to their paths into the university and provides insight into the academically supportive features of their different worlds. Family obligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 25 publications
(31 reference statements)
2
56
0
Order By: Relevance
“…Intergenerational conflicts also occur in many Southeast Asian families (Chhuon, Hudley, Brenner & Macias, 2010;Choi, He, & Harachi, 2008;Shah, 2007). Choi and her colleagues (2008) explained that many Cambodian American and Vietnamese American young people clash with their parents because they adopt more mainstream values.…”
Section: Southeast Asian Americans: the Model Minority Mythmentioning
confidence: 99%
“…Intergenerational conflicts also occur in many Southeast Asian families (Chhuon, Hudley, Brenner & Macias, 2010;Choi, He, & Harachi, 2008;Shah, 2007). Choi and her colleagues (2008) explained that many Cambodian American and Vietnamese American young people clash with their parents because they adopt more mainstream values.…”
Section: Southeast Asian Americans: the Model Minority Mythmentioning
confidence: 99%
“…In addition to understanding the diverse and unique experiences of Southeast Asian groups, research into the second generation have revealed that these gains have been primarily a function of the children of refugees maintaining strong ties to their parents' ethnic community, cultural values, and motivated co-ethnic peers (Chang & Le, 2005;Chhuon, Hudley, Brenner, & Macias, 2010;Supple, McCoy, & Wang, 2010;Zhou & Bankston, 1994, 1998. These findings, together with the greater attainment of the Vietnamese group whose stronger co-ethnic community stands out, highlight the importance of co-ethnic communities in supporting positive outcomes for these refugee groups across generations.…”
Section: Linkages To Outcomes: How Modes Of Incorporation Explain Attmentioning
confidence: 99%
“…Cambodian 1 students in the U.S. present particularly conflicting images in the research literature and in the schools. Research suggest that while Cambodian students tend to be perceived by the larger society through the lens of the model minority stereotype (Ngo and Lee 2007;Reyes 2007), they often endure low expectations from teachers and counselors in their local high schools (Chhuon et al 2010;Um 2003). These local stereotypes cast Cambodian youth as low academic achievers, delinquents, and dropouts.…”
Section: Introductionmentioning
confidence: 99%
“…An ethnic Cambodian identification may be perceived as detrimental to academic success, while a panethnic Asian identity supports a positive academic identity (Chhuon et al 2010;Reyes 2007). It is unclear how Cambodians, whose ethnicity is obscured by a positive panethnic stereotype, might experience this dual identification in school.…”
Section: Introductionmentioning
confidence: 99%